Faktor-Faktor yang Berpengaruh terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan di Kabupaten Purbalingga - Hastuti, Ita Sri; Maryono, Maryono (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
The Land and Building Tax is a fiscal levy imposed by the government on the ownership or utilization of land and buildings. As a primary source of income for local governments, this tax plays a crucial role in supporting various development programs at the local level. Therefore, the aim of this research is to analyze the factors influencing taxpayers' compliance in paying land and building taxes. The research involves taxpayers who own properties such as land and buildings in Purbalingga Regency, totaling 620,626 individuals as the population for this study. The sampling process was conducted using the random sampling technique, with a sample size of 100 taxpayers calculated using the Slovin formula. The research data is primary and obtained through the direct distribution of questionnaires to respondents. To analyze the data, the Multiple Linear Regression method was employed with the assistance of SPSS software version 25. The results of this research indicate that variables such as income, level of education, and tax penalties do not have an impact on the level of taxpayers' compliance with land and building taxes in Purbalingga Regency. On the contrary, it can be concluded that tax knowledge has a positive and significant influence on taxpayers' compliance in paying land and building taxes in Purbalingga Regency.